Effects of temperature on wastewater treatment in an affordable microbial fuel cell-adsorption hybrid system - Tee, Peifang; Mohammad Omar, Abdullah; Tan, I.A.W.; Mohamed Afizal, Mohamed Amin; Cirilo Nolasco, Nolasco-Hipólito; Kopli, Bin Bujang (Elsevier Ltd, 2017)
Graphical abstract: A cost effective single-chamber microbial fuel cell (MFC) integrated with adsorption system was tested under different operating temperatures to observe pH profiles, organics, solids, nutrients, color and turbidity removal and power density generation. The optimum operating temperature range was found to be ∼25-35°C with majority of the removals achieved at ∼35°C. Maximum power density recorded was 74±6mW/m3 with coulombic efficiency (CE) of 10.65±0.5% when operated at 35°C. Present studies had successfully demonstrated the effectiveness of a hybrid system in removing various types of pollutants in POME at optimum temperature and able to fulfill the stringent effluent discharge limit. Chemical oxygen demand (COD), total solids (TS) and turbidity removals increase linearly with temperatures with removal efficiency of 0.5889%C−1, 1.0754%C−1 and 0.7761%C−1, respectively. The temperature coefficient (Q10) is found to be 1.06, 1.45 and 1.09, respectively. Besides, MFC-adsorption hybrid system had demonstrated superior stability over a wide range of operating temperatures in terms of COD removal as compared to the non-integrated MFC system.